Heteroaromatization of Coumarin Part I: Design, Synthesis, Reactions, Antitumor Activities of Novel Pyridine and Naphthyridine Derivatives - Ahmed Borik, Rita Mohammed; El-Wahab, Ashraf Hassan F. A. (Current Organic Synthesis, 2024)
Introduction: A novel series of chromen-3-yl-pyridine moieties were synthesized. IR, NMR, and MS spectroscopy were used to confirm the structure of these novel compounds and study antitumor activity of these compounds. The structure-activity relationship investigation demonstrated that 2,4-diamino- 5-(3-methoxyphenyl)-7-(2-oxo-2H-chromen-3-yl)-1,8-naphthyridine-3-carbonitrile (16), naphthyridine- 3-carbonitrile derivatives 17, 18 and pyrido[2,3-d]pyrimidine derivative 12 were found to be more effective, while compounds 5a,b, 9c, 11, 13 and 14 showed moderate activity for antitumor activities. Objectives: The objective was to design a series of new chromen-3-yl-pyridine and pyrido[2,3-d]pyrimidine derivatives and study the antitumor of these compounds. Materials and Methods: The condensation reaction of 3-acetyl-2H-chromen-2-one with 3-methoxy benzaldehyde and malononitrile or ethyl cyanoacetate in the presence of ammonium acetate and acetic acid under reflux to give the corresponding chromen-3-yl pyridine-3-carbonitrile derivatives. Results: In this study, the antitumor activity of the synthesized compounds chromen-3-yl-pyridine derivatives has been determined for the broad spectrum of cytotoxic activity toward the investigated three cell lines and 5-Fluorouracil, as reference drugs. Conclusion: A series of new chromen-3-yl-pyridine and pyrido[2,3-d]pyrimidine derivatives were synthesized in this work. All compounds were evaluated for cytotoxic activity.
Keywords: aromatic aldehydes